Hubungan Diabetes Melitus dengan Angina Pectoris Berdasarkan Rekam Medis Pasien Rawat Inap di Rumah Sakit Perkebunan Jember Klinik - Ikhda Latifatun; Ervina Rachmawati; Novita Nuraini; Efri Tri Ardianto (Indonesian Journal Publisher, 2024)
Angina pectoris is left chest pain that occurs due to impaired blood flow to the heart, preventing the heart muscle from receiving adequate oxygen. This case ranked third in the top 10 morbidity report at Jember Clinic Plantation Hospital in 2022. The number of morbidity and mortality events of angina pectoris continued to increase from 2020 to 2022. This study aimed to analyze the relationship between diabetes mellitus with angina pectoris based on medical records of inpatients at the Jember Clinic Plantation Hospital. This type of research is quantitative research with a case control study design. The study sample consisted of 164 case and 164 control samples selected using simple random sampling. The results showed that there was a significant association of diabetes mellitus (p value = 0,001) with angina pectoris. The suggestion of this study is that people with diabetes mellitus check their blood sugar regularly to prevent angina pectoris.